Β-Carboline-based molecular hybrids as anticancer agents: a brief sketch. Issue 5 (24th March 2021) - Soni, Jay Prakash; Yeole, Yogesh; Shankaraiah, Nagula
Abstract : The present review elaborates development of β-carboline-based molecular hybrids in past 5 years, their synthesis and biological evaluation. Interestingly, these hybrids have exhibited excellent cytotoxic profile with minimal effect on normal cells. Abstract : Cancer is a huge burden on the healthcare system and is foremost cause of mortality across the globe. Among various therapeutic strategies, chemotherapy plays an enormous role in overcoming the challenges of treating cancer, especially in late stage detection. However, limitations such as extreme side/adverse effects and drug resistance associated with available drugs have impelled the development of novel chemotherapeutic agents. In this regard, we have reviewed the development of β-carboline-based chemotherapeutic agents reported in last five years. The review mainly emphasizes on the molecular hybrids of β-carbolines with various pharmacophores, their synthetic strategies, and in vitro anticancer evaluation. In addition, the mechanisms of action, in silico studies, structural influence on the potency and selectivity among diverse cancer cell lines have been critically presented. The review updates readers on the diverse molecular hybrids prepared and the governing structural features of high potential molecules that can help in the future development of novel cytotoxic agents.